Leishmanicidal activity of biogenic Fe3O4 nanoparticles - Khatami, Mehrdad; Alijani, Hajar; Sharifi, Iraj; Sharifi, Fatemeh; Pourseyedi, Shahram; Kharazi, Sam; Nobre, Marcos Augusto Lima [UNESP]; Khatami, Manouchehr (MDPI, 2017)
Due to the multiplicity of useful applications of metal oxide nanoparticles (ONPs) in medicine are growing exponentially, in this study, Fe3O4 (iron oxide) nanoparticles (IONPs) were biosynthesized using Rosemary to evaluate the leishmanicidal efficiency of green synthesized IONPs. This is the first report of the leishmanicidal efficiency of green synthesized IONPs against Leishmania major. The resulting biosynthesized IONPs were characterized by ultraviolet-visible spectroscopy (UV-Vis), X-ray diffraction (XRD), transmission electron microscopy (TEM), and Fourier transform infrared spectroscopy (FTIR). The leishmanicidal activity of IONPS was studied via 3-4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. The results showed the fabrication of the spherical shape of monodisperse IONPs with a size 4 ± 2 nm. The UV-visible spectrophotometer absorption peak was at 334 nm. The leishmanicidal activity of biogenic iron oxide nanoparticles against Leishmania major (promastigote) was also studied. The IC50 of IONPs was 350 μg/mL. In this report, IONPs were synthesized via a green method. IONPs are mainly spherical and homogeneous, with an average size of about 4 nm, and were synthesized here using an eco-friendly, simple, and inexpensive method.
Keywords: Biosynthesis; IONPs; Iron oxide nanoparticles; Leishmanicidal